2002
DOI: 10.3354/dao048125
|View full text |Cite
|
Sign up to set email alerts
|

Xenoma formation during microsporidial gill disease of salmonids caused by Loma salmonae is affected by host species (Oncorhynchus tshawytscha, O. kisutch, O. mykiss) but not by salinity

Abstract: Host species and salinity often affect the development of disease in aquatic species. Eighty chinook salmon Oncorhynchus tshawytscha, 80 coho salmon O. kisutch and 80 rainbow trout O. mykiss were infected with Loma salmonae. Forty of each species were reared in seawater and 40 in freshwater. The mean number of xenomas per gill filament was 8 to 33 times greater in chinook salmon than in rainbow trout (RBT). Coho salmon had a mean xenoma intensity intermediate to that of chinook salmon and RBT. In contrast to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…To provide a basis for the epidemiology of MGD, the rate of sporulation (xenoma formation) and spore release (xenoma dissolution) has been the subject of intensive investigation, and it has been reported that, in large part, the rate of these processes is determined by water temperature , although the effect of species is not negligible (Ramsay et al 2002). The pathogenesis of MGD has recently been elucidated, and the key events include oral uptake of an infectious spore, intragastric spore germination, a brief residence period in the gut lamina propria, and a 2 wk merogony-like phase in the cardiac subendothelium, followed by a macrophagemediated transport of the parasite to the gill where final development (further merogony and sporogony) occurs within gill pillar cells, with sporogony leading to the formation of a distended spore-filled xenoma (Sánchez et al 2000, Rodríguez-Tovar et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…To provide a basis for the epidemiology of MGD, the rate of sporulation (xenoma formation) and spore release (xenoma dissolution) has been the subject of intensive investigation, and it has been reported that, in large part, the rate of these processes is determined by water temperature , although the effect of species is not negligible (Ramsay et al 2002). The pathogenesis of MGD has recently been elucidated, and the key events include oral uptake of an infectious spore, intragastric spore germination, a brief residence period in the gut lamina propria, and a 2 wk merogony-like phase in the cardiac subendothelium, followed by a macrophagemediated transport of the parasite to the gill where final development (further merogony and sporogony) occurs within gill pillar cells, with sporogony leading to the formation of a distended spore-filled xenoma (Sánchez et al 2000, Rodríguez-Tovar et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that chinook salmon O. tshawytscha and coho salmon O. kisutch are more susceptible to Loma salmonae than rainbow trout (Ramsay et al, 2002). Xenomas degenerated more rapidly and reduced with time in rainbow trout, as compared with the former two species.…”
Section: Discussionmentioning
confidence: 99%
“…Varied host responses among fish species or populations may be related to difference in the susceptibility to microsporidians (Ramsay et al, 2002;Lovy et al, 2007). It has been reported that chinook salmon O. tshawytscha and coho salmon O. kisutch are more susceptible to Loma salmonae than rainbow trout (Ramsay et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Non-genetic studies have suggested there may be strains that differ in host preference (e.g. preferring coho and Chinook salmon to brook or rainbow trout) or showing different infection patterns in salmon versus trout (Bader et al 1998, Shaw et al 2000a,c, Sánchez et al 2001b, Ramsay et al 2002, Lovy et al 2004, Kent & Speare 2005.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Non-genetic studies have suggested there may be strains that differ in host preference (e.g. preferring coho and Chinook salmon to brook or rainbow trout) or showing different infection patterns in salmon versus trout (Bader et al 1998, Shaw et al 2000a,c, Sánchez et al 2001b, Ramsay et al 2002, Lovy et al 2004, Kent & Speare 2005.The present study examined genetic variation across Loma salmonae from the wild, hatcheries, sea netpen farms and laboratories in British Columbia (BC) and Prince Edward Island (PEI), Canada, in California, Colorado, and Idaho, USA, and in Chile to establish the baseline level of variation that we might expect within this species and to look for genetic variants that may correspond to different populations. Genetic data from the type host, rainbow trout Oncorhynchus mykiss in California, is essential as this parasite species is morphologically indistinguishable across its geographic and host range (Morrison & Sprague 1983, Shaw et al 1997, Brown & Kent 2002 and distinct strains or cryptic species may exist.…”
mentioning
confidence: 99%